Morpho-anatomy and physiology of red galangal (Alpinia purpurata) and white galangal (Alpinia galanga) under some salinity stress levels - TIA SETIAWATI; ANIS SUSILAWATI; ASEP ZAINAL MUTAQIN; MOHAMAD NURZAMAN; ANNISA ANNISA; RUHYAT PARTASASMITA; KARYONO KARYONO (Biodiversitas Journal of Biological Diversity, 2018)
Setiawati T, Susilawati A, Mutaqin AZ, Nurzaman M, Annisa, Partasasmita R, Karyono. 2018. Morpho-anatomy and physiology of red galangal (Alpinia purpurata) and white galangal (Alpinia galanga) under some salinity stress levels. Biodiversitas 19: 809-815. Soil salinity is one of the most urgent issues in agriculture as it can reduce plant growth and productivity. Efforts on development of galangal plant on saline soils are still encountering some obstacles such as lack of information on the galangal types that are tolerant to saline condition. The purpose of this study was to determine morpho-anatomical and physiological responses of red galangal (Alpinia purpurata (Vieill.) K. Schum.) and white galangal (Alpinia galanga (L.) Willd.) to salinity stress treatments. This research used a Randomized Block Design (RBD) assigned in a factorial treatment design of two factors, i.e., (i) species of galangal consisting of two levels i.e., red galangal and white galangal, (ii) NaCl concentration consisting of five levels, i.e., 0‰, 3‰, 6‰, 9‰ and 12‰. Each treatment was three replicates. Observation was done on the growth parameters when the plants showed wilting symptoms. The observed data were subjected to Analysis of Variance (ANOVA), followed by a post hoc Duncan Multiple Range Test (DMRT) at ? 5% when the treatment effect was significant. The results showed that salinity stress treatment significantly reduced the plant height increase, leaf area, dry weight, stomata density, chlorophyll content and increased thickness of root epidermis, and proline content in both species of galangal. Red galangal was more tolerant than white galangal.